Intravenous Iron Dextran as a Component of Anemia Management in Chronic Kidney Disease: A Report of Safety and Efficacy. (18th March 2013) - Yessayan, Lenar; Sandhu, Ankur; Besarab, Anatole; Yessayan, Alexy; Frinak, Stan; Zasuwa, Gerard; Yee, Jerry
Abstract : Objective . We aimed to demonstrate safety and efficacy of intravenous (IV) low molecular weight iron dextran (LMWID) during treatment of anemic stage 3 and 4 chronic kidney disease (CKD) patients. Methods. Efficacy data was obtained by retrospective chart review of 150 consecutively enrolled patients. Patients were assigned per protocol to oral or IV iron, with IV iron given to those with lower iron stores and/or hemoglobin. Iron and darbepoetin were administered to achieve and maintain hemoglobin at 10–12 g/dL. Efficacy endpoints were mean hemoglobin and change in iron indices approximately 30 and 60 days after enrollment. Safety data was obtained by retrospective review of reported adverse drug events (ADEs) following 1699 infusions of LMWID (0.5–1.0 g). Results . Mean hemoglobin, iron saturation, and ferritin increased significantly from baseline to 60 days in patients assigned to LMWID (hemoglobin: 11.3 versus 9.4 g/dL; iron saturation: 24% versus 12.9%; ferritin: 294.7 versus 134.7 ng/mL; all P values < 0.0001 ). Iron stores and hemoglobin were maintained in the group assigned to oral iron. Of 1699 iron dextran infusions, three ADEs occurred. Conclusions . Treatment of anemia in CKD stages 3 and 4 with LMWID and darbepoetin is efficacious. The serious ADE rate was 0.06% per infusion.